Ecological Studies and Conservation Strategies of Tree species in Evergreen Forest at Parambikulam Tiger Reserve, Western Ghats, Kerala, India - R, Ranjith; George, Shalu; K, Manjusha; Nawab, Nadirsha P S; Anbazhagi, S; Muthuchamy, Muthukumar (Indian Forester, 2024)
Prerequisite knowledge of the ecosystem is indeed to achieve effective conservation of biodiversity in the Western Ghats. Phytosociological, economical, and ethnobotanical studies may help us understand better the local environment and its current status. From a conservational point of view, such knowledge would help to develop conservation strategies. Phytosociological parameters include density, abundance, frequency, species richness, species evenness, and species diversity in the evergreen forest of Parambikulam Tiger Reserve (PKTR) were discussed. The study also investigated the plants economic and ethnobotanical importance and suggested some necessary conservation strategies for their future survival. Evergreen forests of Parambikualm Tiger Reserve were randomly sampled using the quadrat method, 58 tree species were recorded, represented by 32 families and 51 genera. Monoon fragrans were the dominant species, followed by Dysoxylum malabaricum and Orophea erythrocarpa. The present study conjointly draws attention to the endemic, threatened, medicinal, and economically important tree species of Tiger Reserve. Findings highlighted the need to conserve and enhance biodiversity by recording, evaluating, and assessing the impact through a scientific evaluation. Similar studies can be promoted to minimize biodiversity's consequences from anthropogenic activities and climate change, and for their sustainable management.